Primary Small Cell Carcinoma of the Hypopharynx: A Case Report of a Rare Tumor - Ali Bayram; Ebru Akay; Sema S. Göksu; İbrahim Özcan (Case Reports in Otolaryngology)
Introduction. Primary hypopharynx involvement of small cell carcinoma is very rare and very few cases have been reported in the literature. Here, we report a case of primary small cell carcinoma of the hypopharynx in a male patient. Case Report. A 50-year-old man presented with a 6-month history of sore throat and swellings in the right side of the neck. Direct laryngoscopy and biopsy revealed small cell carcinoma of the hypopharynx located in the right pyriform sinus. Discussion. Small cell carcinoma of the hypopharynx has no clear treatment modality due to the rarity of the disease. Systemic chemotherapy and radiotherapy should have priority among the therapy regimens because of the high metastatic potential of the tumor.